Frost Durability of Steel Fiber Self-Compacting Concrete for Pavements - Jerzy Wawrzeńczyk; Agnieszka Molendowska; Adam Kłak (The Baltic Journal of Road and Bridge Engineering)
The paper presents the results from the research on self-compacting concrete with different steel fibre type addition. The reference self-compacting concrete mix with water/binder = 0.33 was prepared, then modified with steel fibres in the amounts of 0–60 kg/m3 and air entrained with polymer microspheres (40 μm diameter). The major objective of the research was to determine the effect of steel fibre and air content on the self-compacting concrete mix properties and hardened concrete frost durability. The tests also included internal cracking and scaling resistance evaluation for concrete specimens subjected to cyclic freeze-thaw process − two beams were frozen in air and two beams were partially submerged in water and then frozen. The scaling resistance was tested using the slab method on the specimens with sawn surface and on the specimens with natural finished surface. Non-air entrained steel fibre-reinforced concretes, despite their high strength class (C55/67–C60/75) and medium absorption (4.34–5.11%), showed unsatisfactory resistance to internal cracking and scaling tests. The beams partially submerged in water failed after 100 freeze-thaw cycles, which confirms a significant influence of water uptake from moist environment during freeze-thaw cycles and the acceleration of the damage process. Test results indicate that air entrainment with polymer microspheres is a very effective method and allows obtaining very good air pore structure parameters and frost resistance results. The specimens with top − finished surface exhibited less damage in the scaling resistance tests in relation to the specimens with sawn surface.